Rituximab for the treatment of relapsing-remitting multiple sclerosis in Thailand: an economic evaluation and budget impact analysis - Saharat Aungsumart; Saowalak Turongkaravee; Sitaporn Youngkong; Metha Apiwattanakul; Ammarin Thakkinstian; Usa Chaikledkaew (BMC, 2023)
Abstract Background Multiple sclerosis is an inflammatory demyelination process in the central nervous system (CNS) causing neurological disability and poor quality of life. Currently, Thai Food and Drug Administration (FDA)-approved disease-modifying therapy is costly, and most patients with multiple sclerosis are ineligible for treatment in Thailand as previous studies have challenged its cost-effectiveness. Off-label use of rituximab is inexpensive and highly effective in treating multiple sclerosis, but evidence of its cost-effectiveness in Thailand is yet to be collected. Methods This study aimed to evaluate the cost-utility and budget impact of rituximab for multiple sclerosis treatment compared with best supportive care, the standard practice in Thailand to treat the disease. A Markov model with a one-month cycle length and lifetime horizon was applied to compare the costs and outcomes of rituximab and best supportive care based on a societal perspective. Accordingly, incremental cost-effectiveness ratios were estimated. Probabilistic and one-way sensitivity analyses were conducted to investigate parameter uncertainty. In addition, the Markov model was used to assess the 5-year budget impact from the government perspective. Results A rituximab biosimilar demonstrated higher effectiveness and lower associated costs, compared to best supportive care, with the highest probability of being cost-effective (96%). The probability of relapse was the most sensitive parameter according to the one-way sensitivity analysis. The calculated budget impact of treating patients with multiple sclerosis in Thailand was 26,360,000 Thai baht (THB) or 844,255 United States dollars (USD) in the first fiscal year, and approximately 20,810,000-23,080,000 THB (666,608-739,388 USD) in the next four fiscal years. Conclusion In Thailand, a rituximab biosimilar would reduce the overall costs of multiple sclerosis treatment and should, therefore, be included in the National List of Essential Medicines.